(untitled) (CIPEEX, 2022)
INTRODUCTION: THE INTESTINAL OSTOMY IS THE EXTERIORIZATION OF COMPONENTS OF THE GASTRO INTESTINAL TRACT MAKING ITS FIXATION IN THE ABDOMINAL WALL CALLED A COLOSTOMY. THE PATIENT UNDERGOING OSTOMY, PERMANENT OR TEMPORARY, SUFFERS A PROCESS OF ADAPTATION TO ACCEPT HIS NEW CONDITION OF LIFE, THIS NEW CONDITION IS PROBABLY DIFFICULT AND THE ADAPTATION PROCESS IS SOMETIMES TRAUMATIC, BECAUSE IT AFFECTS THE PSYCHOLOGICAL HEALTH, THE PHYSICAL WELLBEING, SELF-ESTEEM, SEXUAL AND PHYSICAL FACTORS OF THE PATIENT (SOUZA, 2004; VIEIRA ET AL 2013). &NBSP;OBJECTIVE: TO IDENTIFY THE SCIENTIFIC LITERATURE THE CHANGES THAT OCCUR IN THE PATIENT COLOSTOMIZADO AND THE RELATIONSHIP WITH THE QUALITY OF LIFE. METHODOLOGY: IS AN INTEGRATIVE LITERATURE REVIEW. THE DATA COLLECTION WAS PERFORMED BY MEANS OF SEARCHING IN SCIENTIFIC JOURNALS ON THE PLATFORM OF THE VIRTUAL HEALTH LIBRARY (VHL) IN THE LILACS, MEDLINE, AND BDENF, AND PLATFORM SCIELO PUBLISHED IN THE PERIOD BETWEEN 2007 TO 2017 (JANUARY TO MARCH), AVAILABLE AT INTEGRA, FREE IN THE PORTUGUESE LANGUAGE.. RESULTS: WE OBSERVED THE DIFFICULTIES OF COLOSTOMIZADO IN THE ADAPTATION PROCESS. NOTE THE ARISING OF NEGATIVE FEELINGS THAT INTERFERE WITH THE QUALITY OF PHYSICAL AND MENTAL HEALTH DURING THE ADAPTATION PROCESS. THE MAIN CHANGES FOUND THAT INTERFERE WITH THE QUALITY OF LIFE OF COLOSTOMY PATIENTS WERE DISCUSSED IN THREE CATEGORIES: SEXUALITY, SOCIAL INTERACTION AND BODY IMAGE. FINAL CONSIDERATIONS: IT IS CLEAR THE FRAGILITY OF THE SUBJECT OSTOMIZADO DURING THE PROCESS OF ADAPTATION OF HIS NEW CONDITION, THEREFORE, IT IS IMPERATIVE FOR THE SUPPORT OF FAMILY MEMBERS AND THE TEAM OF PROFESSIONALS TRAINED TO MEET THESE PATIENTS IN THE HEALTH SERVICE. THE WAY THE PERSON IS SEEN AND OR THE ACCEPTANCE OF THE NEW CONDITION OCCURS, WILL CONTRIBUTE DIRECTLY TO THE QUALITY OF LIFE OF THE SAME, AND THE ISOLATION IS NOT POSITIVE TO COPE WITH THE CONDITION OF COLOSTOMIZED, AND SHOULD BE FACED LOOKING FOR WAYS TO ADAPT AND LIVE WITH THE BAG.IT WAS NOTED THE NEED FOR FURTHER STUDIES IN ORDER TO PROMOTE KNOWLEDGE AND POSSIBLE ACTIONS THAT MAY BE BENEFICIAL FOR PEOPLE’S LIVES COLOSTOMIZED, CONTRIBUTING TO THE QUALITY OF LIFE.